Maresin 1 Attenuates Radicular Pain Through the Inhibition of NLRP3 Inflammasome-Induced Pyroptosis via NF-κB Signaling - Wang, Yi-hao; Li, Yan; Wang, Jun-nan; Zhao, Qing-xiang; Jin, Jin; Wen, Shuang; Wang, Si-cong; Sun, Tao (Frontiers in Neuroscience, 2020)
Background: The exposure of the nucleus pulposus (NP) causes an immune and inflammatory response, which is intrinsically linked to the pathogenesis of radicular pain. As a newly discovered pro-resolving lipid mediator, maresin 1 (MaR1) could exert powerful inflammatory resolution, neuroprotection and analgesic activities. In the present research, the analgesic effect of MaR1 was observed. Then, the potential mechanism by which MaR1 attenuated radicular pain was also analyzed in a rat model. Methods: Intrathecal administration of MaR1 (10 or 100 ng) was successively performed in a rat with non-compressive lumbar disk herniation for three postoperative days. Mechanical and thermal thresholds were determined to assess pain-related behaviour from day1 to day7 (n = 8/group). On the day7, the tissues of spinal dorsal horns from different groups were gathered to evaluate expression levels of inflammatory cytokines (IL-1β, IL-18 and TNF-α), NLRP3 inflammasome and the pyroptosis indicators (GSDMD, ASC, NLRP3, and Caspase-1), together with NF-κB/p65 activation (n = 6/group). TUNEL and PI staining was performed to further examine the process of pyroptosis. Results: After intrathecal administration in the rat model, MaR1 exhibited potent analgesic effect dose-dependently. MaR1 significantly prompted the resolution of the increased inflammatory cytokines levels, reversed the up-regulated expression of the inflammasome and pyroptosis indicators, reduced the cell death and the positive activation of NF-κB/p65 resulting from the NP application on the L5 dorsal root ganglion. Conclusions: This study indicated that the activation of NLRP3 inflammasome and pyroptosis played a significant role in the inflammatory reaction of radicular pain. Also, MaR1 could effectively downregulate the inflammatory response and attenuate pain by inhibiting NLRP3 inflammasome-induced pyroptosis via NF-κB signaling.